ANTIBACTERIAL ACTIVITY OF TEMBELEKAN LEAF (LANTANA CAMARA L.) EXTRACTS AGAINST ESCHERICHIA COLI AND STAPHYLOCOCCUS AUREUS - Mubarak, Fhahri; Rante, Herlina; Putri, Pratami Yona (Fakultas Farmasi, Universitas Muslim Indonesia, 2022)
(Lantana camara L.) is one of the wild plants that can be used to treat various diseases such as skin diseases and diarrhea. The aim of the study to determine the antibacterial activity of ethanol extract of leaf (Lantana camara L.) can inhibit the growth of bacteria Escherichia coli and Staphylococcus aureus. This research was conducted in May 2019 at the Makassar College of Pharmacy. The phase of this research is weighing extracts, extract concentration variant manufacturing process and testing the antibacterial activity of the ethanol extract of tembelekan leaves. The analytical method used is the agar diffusion method. The results showed that the Tembelekan leaves taken from Tana Toraja Regency had a inhibitory effect on the growth of Escherichia coli and Staphylococcus aureus at concentrations of 5, 10 and 20%. The inhibition zone formed in Escherichia coli bacteria was 8.61, 11.57 and 18.67 mm and in Staphylococcus aureus bacteria that was 9.42, 11.68 and 17.34 mm.